Four new species of the genus Draconarius Ovtchinnikov, 1999 (Araneae, Agelenidae) from the Tibetan Plateau, China - Li, Bing; Zhao, Zhe; Chen, Haifeng; Wu, Zhiyan; Li, Shuqiang (Zootaxa, 2019)
Four new species of Draconarius Ovtchinnikov, 1999 (Araneae, Agelenidae) from the Tibetan Plateau, China are described: Draconarius baibaensis sp. n. (♀), Draconarius budanlaensis sp. n. (♀), Draconarius yigongensis sp. n. (♂♀), and Draconarius yingbinensis sp. n. (♀). The male of Draconarius linzhiensis (Hu, 2001) is described for the first time and the female re-illustrated. All species belong to the Draconarius venustus-group. The examined specimens are deposited in the Institute of Zoology, Chinese Academy of Sciences (IZCAS) in Beijing.